2022
DOI: 10.1177/07482337211055131
|View full text |Cite
|
Sign up to set email alerts
|

Cr (III) genotoxicity and oxidative stress: An occupational health risk for leather tannery workers of South Asian developing countries

Abstract: In the leather industry, Cr (III) is used as a basic tanning agent. The wastewater discharged from the tannery industry contains a high concentration of chromium. Recent studies indicate the genotoxic effects especially DNA damage and oxidative stress of Cr (III) in tannery workers. Cr (III) interacts with DNA to form DNA cross-links and DNA strand breaks. It also modifies the oxidative DNA base through the Haber–Weiss reaction. The present study is based on an overview of scientific literature and previous ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…Extensive research has focused on exploring the role of Cr(III) as an essential trace element essential for maintaining normal bodily functions. However, several investigators noted that exposure of tannery workers to Cr(III) compounds such as CrK(SO 4 ) 2 and CrCl 3 resulted in DNA damage and oxidative stress (Dubey et al, 2022; Vincent, 2017; Zhang et al, 2008). These findings emphasize the importance of conducting additional investigations to examine the pharmacological properties of Cr(III) in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive research has focused on exploring the role of Cr(III) as an essential trace element essential for maintaining normal bodily functions. However, several investigators noted that exposure of tannery workers to Cr(III) compounds such as CrK(SO 4 ) 2 and CrCl 3 resulted in DNA damage and oxidative stress (Dubey et al, 2022; Vincent, 2017; Zhang et al, 2008). These findings emphasize the importance of conducting additional investigations to examine the pharmacological properties of Cr(III) in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The Cr(III) compounds selected were CrK(SO 4 ) 2 and CrCl 3 , while Cr(VI) compounds included CrO 3 , K 2 CrO 4 , K 2 Cr 2 O 7 , and Na 2 Cr 2 O 7 . The doses were calculated based upon the concentration of Cr contained in the 20 mg/kg dose of CrO 3 (positive control) and on the published genotoxic doses reported for Cr compounds ([Cr] = 10 mg/kg ± 1/3) according to the OECD and EPA guidelines (Dubey et al, 2022; EPA, 1998; Fang et al, 2014; García‐Rodríguez, Santiago‐Moreno, et al, 2023; Itoh & Shimada, 1996; OECD, 2016; Sawicka et al, 2021; Wang et al, 2006). Mice were randomly assigned to the following groups ( n = 5 mice per group), and subsequent assessments were performed: Cr(III) versus Cr(VI) Control; a group of females and another group of males were treated only with the vehicle. Cr(III); two groups of females and two groups of males were i.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report by Environment Texas reported the discharge of Cr waste into Calaveras Lake, San Antonio, Texas, posing a potential risk to public health [23]. Leather tanning industries contribute to the extreme Cr contamination in South East Asia, risking the workers to various health hazards [24]. Environmental and health advocates indicated that the Cr contamination in Calaveras Lake threatens the health of anglers, boaters, and people who eat fish from the lake [23].…”
Section: Introductionmentioning
confidence: 99%